Brief Periods of Nitric Oxide Inhalation Protect Against Myocardial Ischemia-Reperfusion Injury - Nagasaka, Yasuko (2008)
BACKGROUND: Prolonged breathing of nitric oxide reduces myocardial ischemia-reperfusion injury but the precise mechanisms responsible for the cardioprotective effects of inhaled nitric oxide are incompletely understood. METHODS: We investigated the fate of inhaled nitric oxide (80 parts per million) in mice, and quantified the formation of nitric oxide metabolites (NO-metabolites) in blood and tissues. We tested whether the accumulation of NO-metabolites correlated with the ability of inhaled nitric oxide to protect against cardiac ischemia-reperfusion injury. RESULTS: Mice absorbed nitric oxide in a nearly linear fashion (0.19±0.02 μmol/g·h). Breathing nitric oxide rapidly increased a broad spectrum of NO-metabolites. Levels of erythrocytic S-nitrosothiols, N-nitrosamines and nitrosyl-hemes exceeded nitrite within 30 sec of commencing nitric oxide inhalation. Marked increases of lung S-nitrosothiols and liver N-nitrosamines levels were measured, as well as elevated cardiac and brain NO-metabolite levels. Breathing hypoxic concentrations potentiated the ability of inhaled nitric oxide to increase cardiac NO-metabolite levels. Concentrations of each NO-metabolite, except nitrate, rapidly reached a plateau and were similar after 5 and 60 minutes. Studying a murine cardiac ischemia-reperfusion injury model, breathing nitric oxide for either 5 or 60 min before reperfusion decreased MI/AAR by 31 and 32%, respectively. CONCLUSIONS: Breathing nitric oxide leads to the rapid accumulation of a variety of NO-metabolites in blood and tissues, contributing to the ability of brief periods of nitric oxide inhalation to provide cardioprotection against ischemia-reperfusion injury. The NO-metabolite concentrations achieved in a target tissue may be more important than the absolute amounts of nitric oxide absorbed.